Development of Competitive Strategy in the Handheld Mobile Computing Industry (Case Study: PT. XYZ) - Restianti, Vika; Ma'arif, Mohamad Syamsul; Asikin, Zaenal (Indonesian Journal of Multidisciplinary Science, 2025)
The rapid growth of the handheld mobile computing industry in Indonesia has intensified the need for effective digital solutions across critical sectors, including logistics, retail, and manufacturing. Despite this potential, many companies struggle to identify competitive strategies that leverage their internal resources while responding to dynamic external environments. This study, Development of Competitive Strategy in the Handheld Mobile Computing Industry (Case Study: PT. XYZ), aims to formulate an optimal competitive strategy for PT XYZ by applying a comprehensive analytical framework that integrates the Resource-Based View (RBV), VRIO, PESTEL, Five Forces, SWOT, and Quantitative Strategic Planning Matrix (QSPM). Data were collected through in-depth interviews with key management personnel and analyzed using a qualitative descriptive approach. The findings indicate that PT XYZ possesses significant competitive advantages, including strong bulk purchasing capabilities, a positive customer reputation, strategic partnerships, and a solution-oriented organizational culture focused on customer satisfaction. Based on QSPM analysis, the study recommends prioritizing a product development strategy that emphasizes greater product diversification and enhanced device compatibility to strengthen market position. These results highlight the importance of aligning internal strengths with external market opportunities, providing actionable insights for managers seeking to enhance competitiveness in a rapidly evolving digital industry. The study also offers implications for other firms in similar sectors to strategically leverage their unique resources to maintain sustainable growth and adapt to technological advancements.